Bathing suit ichthyosis. - Milano, A. (European Journal of Pediatric Dermatology, 2016)
Bathing suit or thermosensitive ichthyosis (BSI) is an autosomal recessive lamellar ichthyosis, clinically characterized by location on the trunk and summer worsening. It is one of the three variants of lamellar ichthyosis together with the classical form extended to the entire skin surface and present at birth as collodion baby, and the self-healing form. All three variants are linked to mutations of transglutaminase 1 (TGase1) gene. The latter is present in the upper layer of the epidermis where it facilitates the formation of the cell keratin envelope with formation of cross-links between structural proteins as loricrin and involucrin. Oji et al. showed that the phenotype of BSI is influenced by the body temperature because the transglutaminase activity of the mutated TGase1 significantly decreases at temperatures higher than 33° C (1). Hypohidrosis related to obstruction of sweat ducts by the scales is a likely aggravation factor (2).